2003
DOI: 10.1124/dmd.31.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CYP3A4 Expression in Human Hepatocytes by Pharmaceuticals and Natural Products

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Human CYP3A4 metabolizes a majority of clinically important substrates at variable rates. Accounting for these unpredictable rates is the wide variation noted in expression of this enzyme that is due, in part, to xenobiotic exposure. We used primary cultures of human hepatocytes from 17 individuals to assess the inducibility of CYP3A4 mRNA by prototypical inducers, dietary flavonoids, and botanicals. Those agents producing the greatest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(136 citation statements)
references
References 23 publications
7
125
1
Order By: Relevance
“…However, this same concentration of PHY does not activate hPXR significantly in either HepG2 or Huh7 cells as assessed by CYP2B6 reporter gene activity. These results are in agreement with a previous report by Raucy et al (29), where only minor activation of PXR was observed with PHY at concentrations up to 1 mM in HepG2 cells (29). These initial results provided the first inclination that hPXR may not be the primary mediator of PHY induction of CYP2B6 gene expression.…”
Section: Phy Activates and Translocates Hcar In Vivo Insupporting
confidence: 83%
“…However, this same concentration of PHY does not activate hPXR significantly in either HepG2 or Huh7 cells as assessed by CYP2B6 reporter gene activity. These results are in agreement with a previous report by Raucy et al (29), where only minor activation of PXR was observed with PHY at concentrations up to 1 mM in HepG2 cells (29). These initial results provided the first inclination that hPXR may not be the primary mediator of PHY induction of CYP2B6 gene expression.…”
Section: Phy Activates and Translocates Hcar In Vivo Insupporting
confidence: 83%
“…However, when a reporter gene assay with hPXR was used, quercetin did not show a significant increase in luciferase activity, suggesting that CYP3A4 was induced by mechanisms not involving PXR. Herbs like grapeseed extract, ginseng, garlic, and kava-kava also increased CYP3A4 mRNA levels in hepatocytes, but of these botanicals, only kava-kava produced enhanced luciferase activity [61]. The results of that study clearly showed that some CAMs have the potential to induce CYP3A4, although not always mediated via PXR.…”
Section: In Vitrosupporting
confidence: 52%
“…Raucy [61] used CYP3A4 mRNA analysis in primary cultures of human hepatocytes of 17 individuals to test the inductive properties of several flavonoids, including quercetin, resveratrol, and curcumin. Of these, only quercetin produced accumulation of CYP3A4 mRNA.…”
Section: In Vitromentioning
confidence: 99%
“…To further elucidate the involvement of PXR, a reporter gene assay with hPXR was used. Quercetin did not show a significant increase in luciferase activity, suggesting that CYP3A4 was induced by mechanisms not involving PXR (105). Kava-kava also increases CYP3A4 mRNA levels in hepatocytes with enhanced luciferase activity, others like grapeseed extract, ginseng and garlic stimulates only CYP3A4 mRNA without increasing luciferase activity indicating that that the induction CYP3A4 by some herbs may not always be mediated via PXR.…”
Section: Investigating Herb-drug Interactionmentioning
confidence: 90%